Fetal vascular adaptation before and after treatment of severe maternal anemia in pregnancy. Issue 3 (17th February 2016) - Ali, Eram; Kumar, Manisha; Naqvi, Sayyed E.H.; Trivedi, Shubha S.; Singh, Anuradha
Abstract: Objectives: To use color Doppler ultrasonography indices to study the effects on fetal circulation of treating severe maternal anemia. Methods: A prospective cohort study enrolled patients who were at 30–34 weeks of pregnancy and had hemoglobin levels below 70 g/L between November 1, 2011 and March 31, 2013 at a hospital in New Delhi, India. A control group consisting of patients with the same duration of pregnancy and with hemoglobin levels above 110 g/L was included. Umbilical artery and middle cerebral artery velocimetry were performed using color Doppler ultrasonography at admission and after 4 weeks and 6 weeks of treatment. Results: The maternal anemia cohort demonstrated a significantly lower middle cerebral artery resistance index and middle cerebral/umbilical artery resistance ratio ( P < 0.001) at admission. Following 4 weeks of treatment for maternal anemia, significant increases in these parameters were observed ( P < 0.001). Conclusion: Fetuses of individuals with severe maternal anemia demonstrated altered cerebral and umbilical artery flows. Normal flows were restored following treatment of maternal anemia.